Dialogare: compendio di biologia - Frizzi, Filippo (Strumenti per la didattica e la ricerca, 2017)
The compendium collects the basic themes of biology in a very simplified form, ideally following the programmatic criteria of secondary school. The didactic program is articulated starting from the molecules that make up living organisms to end at the theoretical basis of ecology and environmental protection. All the main topics of life sciences such as genetics, anatomy and the evolution of organisms are addressed, always trying to convey the heart of the theoretical concept through a simple but adequate terminology. The goal is to offer a first look at the basis of biology to those who intend to carry out an in-depth study of this subject, which is extremely fascinating but also decidedly complex, vast and multifaceted.